KONSEP KEADILAN DALAM FILSAFAT HUKUM DAN FILSAFAT HUKUM ISLAM (UINSI Samarinda, 2015)
This paper compares the concept of justice in the viewpoint of legal philosophy and the philosophy of Islamic law. Justice in Islamic law comes from the Creator, Allah Swt., which is infinite justice and therefore must be believed not to apply the law unless justice to His servants. The concept of Justice will continue to evolve in line with social development. Fairness in life becomes an important requirement for humans so that everyone can strike a balance between demanding their rights and carrying out their obligations in an effort to reach the truth. Thus, the truth and the obligations must be in harmony and balance in life. Law is just a collection of words when the law does not materialize justice. When a law does not recognize justice, it is meaningless. Law formulation, therefore, is the process of harmonizing legal certainty and proportionality.